Methodology use of information and measurement systems sigma in the manufacturing process aircraft - Лещенко, О.О.; Щербак, Л.М. (Proceedings of National Aviation University (archive), 2006)
The Methodology of the use information-measuring systems Sigma in process production plane. The Considered methodology of the use information-measuring systems in aircraft area on base IVS type Sigma 2030, which provides the measurements linear and angular sizes of the complex details of the plane in 3-h measured Euclidean space. The Advantage such ІVS there is undertaking the benchmark analysis digital designed copies of the detail with result of the measurements of the geometric sizes of the made detail.